Tradition, Truth, and History in Theology: Four Recent Proposals. - Scordino, Anthony J. (Modern Theology, 2025)
The article focuses on how contemporary Catholic theologians are engaging the enduring tensions between tradition, truth, and historical consciousness in theology. Topics include Thomistic critiques of nouvelle théologie's David Bentley Hart's eschatological reframing of tradition, and Anne Carpenter's constructive view of history as a mediating force in Christian doctrine.